2010
DOI: 10.1016/j.brainres.2009.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levetiracetam on hippocampal kindling in Noda epileptic rats

Abstract: In order to clarify the seizure susceptibility of Noda epileptic rat (NER) and the antiepileptic effects of levetiracetam (LEV), we performed electrical hippocampal kindling in NERs compared with Wistar rats (experiment 1), and hippocampal kindling in NERs with LEV administration (experiment 2). In experiment 1, electrical stimulation was administered to the right dorsal hippocampus of NERs and Wistar rats once per day. In experiment 2, NERs were randomly assigned to group L (LEV administration) and C (saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Ishimaru et al . reported the antiepileptic effects of LEV on hippocampal kindling in NERs [ 49 ], and Inoue et al . also showed inhibition effects of traditional AEDs, phenobarbital (PB) and valproate (VPA), against seizures evoked by strong environmental stimuli in mature NERs [ 45 ].…”
Section: Generalized Tonic-clonic Seizure Models: Ier Ner and Wermentioning
confidence: 99%
“…Ishimaru et al . reported the antiepileptic effects of LEV on hippocampal kindling in NERs [ 49 ], and Inoue et al . also showed inhibition effects of traditional AEDs, phenobarbital (PB) and valproate (VPA), against seizures evoked by strong environmental stimuli in mature NERs [ 45 ].…”
Section: Generalized Tonic-clonic Seizure Models: Ier Ner and Wermentioning
confidence: 99%
“…Several other studies have also shown beneficial effects of LEV treatment in acute seizure models. For example, the development of kindling (a progressive increase in seizure severity induced by repeated brain stimulation at certain intervals), and kindling-related abnormal gene expression can be considerably modulated through daily application of LEV (15, 21, 22). …”
Section: Usefulness Of Lev For Easing Epileptogenesismentioning
confidence: 99%
“…Several studies report promising outcomes such as delayed development of hippocampal hyperexcitability, restraint of electrographic seizures, diminishment in the abnormal migration of newly born neurons into the dentate hilus, and inhibition of inflammatory responses in SE models (20, 26, 27, 29). There are also reports of mitigation of synaptic potentiation and abnormal expression of IEGs, and prevention of abnormal accumulation of 7S SNARE complexes and SV2 in kindling models (15, 2224). However, some studies report no beneficial effects of LEV treatment after SE in terms of easing epileptogenesis or cognitive dysfunction (31, 32).…”
Section: Overall Conclusionmentioning
confidence: 99%